Preventing organ damage by genetic testing for hereditary haemochromatosis - M.J. Kotze; J.N.P. de Villiers; S.W. van der Merwe (South African Family Practice)
The rapid discovery of several iron-related genes in the last 10 years has led to the development of cost-effective genetic assays for early diagnosis of hereditary haemochromatosis (HH). A genetic predisposition for this relatively common autosomal recessive disease has been identified in approximately 1 in 100 South Africans of European descent. If left untreated, this condition may lead to organ damage presenting as cirrhosis, liver cancer, diabetes, arthritis, impotence, sterility and/or cardiac disease. Due to the fact that serum iron parameters are frequently affected by factors such as liver disease and inflammation, direct mutation detection has become the method of choice for accurate diagnosis of inherited iron overload in patients with elevated iron stores. Haemochromatosis can be prevented by regular blood donation or phlebotomy and therefore detection of a genetic predisposition at an early age, before irreversible damage to cardiac, hepatic and endocrine tissue occurs, represents an important clinical goal.